Clinical and Laboratory Characteristics of Febrile Seizure in Children Presenting with Seizure - Gupta, Murli Manohar; Sah, Shyam Nandan (Journal of Nepalgunj Medical College, 2022)
Introduction: Febrile seizures are generally defined as seizures occurring in children from 6 months to 60 months of age in association with a fever greater than 38°C (100.4°F), who do not have evidence of an intracranial cause (e.g. infection, head trauma, and epilepsy), another metabolic cause of seizure (e.g. electrolyte imbalance, hypoglycemia, drug use, or drug withdrawal), or a history of an afebrile seizure. Aims: To find clinical and laboratory characteristics of febrile seizure. Methods: A hospital based cross sectional study was performed in Nepalgunj Medical College, Kohalpur, Banke from March 2021 to February 2022. Children of aged 6 months to 60 months, with fever and seizure admitted in Department of Pediatrics and visiting in outdoor fulfilling inclusion criteria were taken for the study. Detailed history and examination was performed, Data related to age, sex, family history, recurrence and relevant investigations was carried out in all patients. Results: Out of 3294 admitted patients, 82 children with febrile seizure were studied, in which 55 (67.1%) male and 27 (32.9%) were female respectively which accounts for 2.03:1 ratio. Majority of 34 (41.46%) belongs to 13-24 months of age. 70 (85.4%) had children simple febrile seizure and 12 (14.6%) had complex febrile seizure. 25 (30.5%) had recurrence history. Majority of children had history of cough 26 (31.7%). Mean total leukocyte count (TLC) was slightly higher and other are within normal range. Conclusion: Febrile seizure is more common in male, majority of children affected are below two years of age. Simple febrile seizure is more common variety.